Pembuatan dan Karakterisasi BPAC (Banana Peels Activated Carbon) Sebagai Biosorben Logam Raksa (Hg) dengan Aktivator HCl - Putri Ade Rahma Yulis; Asyti Febliza (Jurnal Riset Kimia, 2023)
Based on the 2021 Central Statistics Agency (BPS) about environment, there is still a high level of pollution, especially pollution in water. The pollution is dominated by heavy metal contaminants. This research was carried out to make and characterized biosorbents which were activated into activated carbon from banana peel waste called BPAC (Banana Peels Activated Carbon) with HCl activator. Activated carbon has many advantages as an adsorbent with time and cost efficiency in absorbed heavy metals. Activated carbon from banana peels that has been formed was tested for its characterization included tests for water content, ash content, and iodine absorption and compared with SNI standard activated carbon quality with results of 3.9% water content, 6.2% ash content and iodine absorption 563.6 mg/g. The functional groups were tested by FT-IR (Fourier Transform-Infra Red) with the result spectrum at the peak of 3334 cm-1, 2921 cm-1,  2853 cm-1, 1575 cm-1, 1375 cm-1, and 1098 cm-1 which indicated the presence of functional groups such as (C-O); (C=O); (C-H); (O-H) of several compounds such as lignin, pectin, cellulose and galacturonic acid as active sites that can bind heavy metals such as mercury. Surface morphology of activated carbon was tested by SEM (Scanning Electron Microscopy) with 500x and 1000x magnification. Activated carbon that has been tested is then applied to artificial mercury metal waste to determine the adsorption power and effectiveness of the activated carbon. Mercury metal content before adsorption was 6.995 mg/L and after adsorption was 0.0084 mg/L which was measured used ICP-OES (Inductively Coupled Plasma – Optical Emission Spectrometry). The percentage effectiveness of BPAC (Banana Peels Activated Carbon) reaches 99.87% with an adsorption capacity of 0.698 mg/g. Based on the results of this percentage it can be said that BPAC is effective to be used as a metal mercury biosorbent.